2021
DOI: 10.1029/2021ja029587
|View full text |Cite
|
Sign up to set email alerts
|

A 3D MHD‐Particle Tracing Model of Na+ Energization on Mercury's Dayside

Abstract: Mercury has been a target of interest and study since the flybys by Mariner 10 in 1974 and 1975 and has been subject to intense subsequent study by the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft (Solomon et al., 2007), which orbited Mercury from 2011 until early 2015. As many previous works have noted, Mercury occupies a unique place among the solar system's planets. It is situated closest to the Sun, in a plasma and magnetic environment that is an order of magnitude m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…This process could be similar to the pickup process of Na + test particles shown in Glass et al. ( 2021 ). Those authors suggested that the large‐scale magnetospheric convection electric field energized Na + test particles from very low altitudes on the dayside enough that they could gyrate through the magnetopause.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This process could be similar to the pickup process of Na + test particles shown in Glass et al. ( 2021 ). Those authors suggested that the large‐scale magnetospheric convection electric field energized Na + test particles from very low altitudes on the dayside enough that they could gyrate through the magnetopause.…”
Section: Discussionmentioning
confidence: 59%
“…If they could reach high enough altitudes, they would then be accelerated by the convection electric field in the entry layer, which was driven by the potential drop associated with the dayside magnetopause reconnection since the magnetic field lines in the entry layer were newly opened by the magnetopause reconnection. This process could be similar to the pickup process of Na + test particles shown in Glass et al (2021). Those authors suggested that the large-scale magnetospheric convection electric field energized Na + test particles from very The Flux of Na + -group Ions Near Mercury's Surface Underneath the Cusp, Which Corresponds to the Pitch Angle-Energy Distribution in Figure 7 low altitudes on the dayside enough that they could gyrate through the magnetopause.…”
Section: Solar Wind Ions Sputteringmentioning
confidence: 65%
See 1 more Smart Citation
“…The test‐particle trajectory in Figure 3 seems to suggest that the Population 2 ions in Region A does not belong to the Type 0 or Type 1 ion populations described in Glass et al. (2021), but could be part of Type 3. Glass et al.…”
Section: Discussionmentioning
confidence: 72%
“…The test-particle trajectory in Figure 3 seems to suggest that the Population 2 ions in Region A does not belong to the Type 0 or Type 1 ion populations described in Glass et al (2021), but could be part of Type 3. Glass et al (2021) identified different types of Na + test-particle trajectories which could be responsible for the population of > 1 keV Na + ions observed in Mercury's northern magnetospheric cusp by FIPS (Raines et al, 2014). Type 0 ions pass through the magnetosheath before crossing the northern cusp, while Type 1 ions move directly into the northern cusp without passing through or coming near the magnetosheath boundary.…”
Section: Discussionmentioning
confidence: 98%